Relationship between micronutrients and rheumatoid arthritis - Qian Xu; Zhen Chang; Jingjing Lv; Yong Zhang (Medicine, 2026)
Micronutrients play synergistic roles in rheumatoid arthritis (RA), but few have been thoroughly investigated, and causal relationships remain unclear. We employed Mendelian randomization (MR) using GWAS data to assess the causal effect of serum micronutrients on RA. Additionally, we conducted a cross-sectional study using NHANES data (2001–2006) among adults aged ≥ 20 years (n = 9015, both sexes) to evaluate the association between serum β-carotene and RA using weighted multivariate regression and Cox models. MR analysis indicated a causal association between serum β-carotene and RA (OR = 1.35, 95% CI: 1.14–1.60, P = 5.53E-04). NHANES analysis showed that higher serum β-carotene levels were linked to lower RA prevalence (OR = 0.80, 95% CI: 0.65–0.97) and reduced all-cause mortality (HR = 0.76, 95% CI: 0.67–0.87). Age and smoking modified these associations. A linear inverse relationship was observed between serum β-carotene and RA (P-non-linear = 0.992), and serum levels weakly correlated with intake ( R = 0.3032, P < .001). Serum β-carotene is causally and inversely associated with RA and may reduce all-cause mortality. Further studies are warranted to validate these findings.